High‐Frequency Mutations in TP53, AXIN1, CTNNB1, and KRAS, and Polymorphisms in JAK1 Genes Among Mongolian HCC Patients - Nomin Bold; Khurelsukh Buyanbat; Ariya Enkhtuya; Nomin Myagmar; Gerelsuren Batbayar; Zolzaya Sandag; Dolgion Damdinbazar; Nomuun Oyunbat; Tuul Boldbaatar; Ankhbayar Enkhbaatar; Gan‐Erdene Baatarjav; Taivan Nanzaddorj; et al. (Cancer Reports)
ABSTRACT Background Mongolia has the highest incidence of liver cancer worldwide, largely driven by a high prevalence of hepatitis virus infections. Mutations in oncogenes and tumor suppressor genes provide valuable insights into the molecular mechanisms of hepatocellular carcinoma (HCC). Aims This study aimed to investigate the prevalence of mutations in key oncogenes and tumor suppressor genes in Mongolian HCC patients and to explore their molecular mechanisms, particularly in relation to hepatitis virus infections. Methods and Results We analyzed 55 tumor tissue samples from Mongolian HCC patients (2019–2021), identifying mutations in TP53, CTNNB1, AXIN1, KRAS, and JAK1 through sequencing. Western blotting was used to assess β‐catenin and p53 protein levels. Our findings showed p53 overexpression in tumors with TP53 mutations (F270I and S362S), while mutations such as R213* and a short‐sequence deletion upstream of intron 7 produced premature stop codons, resulting in truncated p53 and loss of tumor suppressor function. β‐catenin accumulation was observed in tumors with CTNNB1 mutations (D32N/Y, S33C/Y, S34V, S37P, T41A, and S45P). CCND1 expression, a key target of the Wnt/β‐catenin pathway, was significantly upregulated in tumors harboring CTNNB1 and AXIN1 mutations (p = 0.02213). Statistical analysis revealed a positive correlation between β‐catenin and CCND1 expression levels (r = 0.42703). Hepatitis virus infections were significantly associated with these mutations (p < 0.01), suggesting a link between viral infection and genetic alterations in HCC development. Compared to TCGA data, our cohort displayed a significantly higher mutation frequency (p < 0.001 and p < 0.05), indicating potential regional genetic and environmental influences. Conclusion This study provides insights into the molecular mechanisms of HCC in Mongolia, highlighting distinct mutational patterns in TP53, CTNNB1, AXIN1, and KRAS. The association between hepatitis virus infections and these mutations underscores their potential oncogenic impact and may inform future therapeutic strategies for HCC in this population.